Randomised controlled trial on the effectiveness of audible timed reminders for simulated serial pain score documentation in an Emergency Department - Ng, Von How; Ahmad Khaldun Ismail; Siti Sarah MZ; Ida Zarina Zaini (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Pain is one of commonest presentations at Emergency Department (ED). Previous studies showed inadequate pain control in ED. However, few have addressed specific, practical methods of improving the timeliness and frequency of pain control in emergency setting. This study was a randomized controlled trial in a simulated environment of an actual functioning ED using a timer device to remind care personnel to assess pain and provide analgesia at set intervals versus a “standard therapy” group without visual/audio aids. The mean documentation performance scores between timer and control groups were 94.45% + 5.85 vs 72.22% + 17.57 (p<0.05) respectively. The use of timer device did not appear to have any effect on the timeliness of recording the first pain score observation following analgesia, 1.74 min + 0.41 (timer) vs 1.78 min + 0.82 (control) (p=0.89). The documentation performance score showed 50% of the timer device group recorded only one omission compared to 90% of control group recorded more than one omission. The range of observations time for the control group is widespread (min: 4 minutes, max: 36 minutes) compared to the intervention group (min: 11 minutes, max: 22 minutes). The median time intervals for pain score documentations per subject in both groups were 15 minutes, however, the IQR in timer group was 1 compared to 7 in control group. In conclusion, the addition of timer device had the advantage to improve documentation performance score and subsequently the serial pain score documentation in ED.